2008
DOI: 10.1111/j.1460-9568.2008.06470.x
|View full text |Cite
|
Sign up to set email alerts
|

Uncoupling of interleukin‐6 from its signalling pathway by dietary n‐3‐polyunsaturated fatty acid deprivation alters sickness behaviour in mice

Abstract: Sickness behaviour is an adaptive behavioural response to the activation of the innate immune system. It is mediated by brain cytokine production and action, especially interleukin-6 (IL-6). Polyunsaturated fatty acids (PUFA) are essential fatty acids that are highly incorporated in brain cells membranes and display immunomodulating properties. We hypothesized that a decrease in n-3 PUFA brain level by dietary means impacts on lipopolysaccharide (LPS)-induced IL-6 production and sickness behaviour. Our results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
71
2
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 88 publications
(88 citation statements)
references
References 68 publications
9
71
2
1
Order By: Relevance
“…In vivo, chronic dietary LC n-3 PUFA deficiency significantly affected microglia activity and increased the release of IL-6 and TNF-α in the blood of rat (McNamara et al, 2010) and in the hippocampus of mice at post-natal day 21 (Madore et al, 2014), which was not observed in the brain of adult and aged mice (Delpech et al, 2015c;Mingam et al, 2008;Moranis et al, 2012). Alternatively, both in vivo and in vitro studies have reported anti-inflammatory activities of LC n-3 PUFA in the brain especially in microglia (Laye, 2010;Orr and Bazinet, 2008) and currently supports: 1) a capacity to down-regulate the activity of proinflammatory transcription factors such as NF-κB, 2) an inhibitory role on the release of cytokines, such as interleukin IL-1β and TNF-α, from activated microglia, 3) an inhibitory action against the production of NO and PGE2 in response to microglia activation, 4) a beneficial action on membrane lipid composition, lipid rafts and membrane receptors incorporation such as TLR receptors, and 5) a capacity to elicit peripheral and central proresolutive processes by activating phagocytosis and promoting polarization of glial cells toward a M2-like phenotype.…”
Section: Mechanisms Of Action Of N-3 Pufa In Controlling Neuroinflammmentioning
confidence: 91%
“…In vivo, chronic dietary LC n-3 PUFA deficiency significantly affected microglia activity and increased the release of IL-6 and TNF-α in the blood of rat (McNamara et al, 2010) and in the hippocampus of mice at post-natal day 21 (Madore et al, 2014), which was not observed in the brain of adult and aged mice (Delpech et al, 2015c;Mingam et al, 2008;Moranis et al, 2012). Alternatively, both in vivo and in vitro studies have reported anti-inflammatory activities of LC n-3 PUFA in the brain especially in microglia (Laye, 2010;Orr and Bazinet, 2008) and currently supports: 1) a capacity to down-regulate the activity of proinflammatory transcription factors such as NF-κB, 2) an inhibitory role on the release of cytokines, such as interleukin IL-1β and TNF-α, from activated microglia, 3) an inhibitory action against the production of NO and PGE2 in response to microglia activation, 4) a beneficial action on membrane lipid composition, lipid rafts and membrane receptors incorporation such as TLR receptors, and 5) a capacity to elicit peripheral and central proresolutive processes by activating phagocytosis and promoting polarization of glial cells toward a M2-like phenotype.…”
Section: Mechanisms Of Action Of N-3 Pufa In Controlling Neuroinflammmentioning
confidence: 91%
“…In vivo, chronic dietary n-3 PUFA deficiency significantly increased the production and release of IL-6 and TNFa in the blood (McNamara et al, 2010). In addition, mice exposed throughout life to a diet devoid of n-3 PUFAs displayed lower brain DHA level and higher LPSinduced IL-6 in the plasma and in the hippocampus (Mingam et al, 2008). With aging, IL-6 expression was increased in the cortex of both n-3 deficient and n-3 adequate mice while IL-10 expression was decreased with no effect of long term a-LNA deficient or enriched diet (Moranis et al, 2011) (figure 4).…”
Section: Consequences Of the Decrease In N-3 Pufas On Age-related Neumentioning
confidence: 95%
“…The remainders were allowed to clot and sera were separated by centrifugation (3500 rpm, 20 min, 25°C) and used freshly for determination of serum levels of fasting glucose [12], Insulin [13] and the lipid profile (T-Chol [14], HDL-C [15] and TG (16)] were analyzed using Synchron CX5 autoanalyzer (Beckman, USA) and LDL-cholesterol levels were calculated by using the Falholt et al formula [17]. Also, pro-inflammatory markers; Tumor Necrosis Factor (TNF)-α [18], interleukin (IL)-6 [19] cleaved to the N-terminal-proBNP(NT-proBNP) and BNP upon ventricular myocyte stretch. In practice, there is increasing recognition of the importance of BNP in the pathophysiology, diagnosis, prognosis and treatment of left ventricular dysfunction in selected patient groups [22][23][24], and other studies have shown an association of proBNP with subclinical cardiovascular diseases [25,26].…”
Section: Blood Sampling and Biochemical Analysesmentioning
confidence: 99%